Safety and effect on reported symptoms of depigmented polymerized allergen immunotherapy: a retrospective study of 2927 paediatric patients. Issue 3 (May 2015) - Pfaar, Oliver; Sager, Angelika; Robinson, Douglas S.
Abstract: Background: Allergen immunotherapy (AIT) is effective treatment for allergic diseases, and subcutaneous use of depigmented polymerized extracts may allow rapid up‐dosing and safe therapy. To date, there is little information on their safety and clinical effects for children and adolescents with allergic disease. Methods: We performed a retrospective survey of patient notes of 2927 children and adolescents across 136 centres who had received subcutaneous AIT (SCIT) with depigmented polymerized extracts to pollen or mite allergens for at least 1 yr to collect documentation on safety and clinical symptoms. Results: 16.3% percent of patients had local reactions, of these 148 were larger than 12 cm in diameter. Systemic reactions were documented in 1.6% of children and in 0.8% of adolescents. There were no documented cases of anaphylactic shock. There were significant reductions in the frequency of patients with recorded nasal symptoms over time of treatment. Moreover, the prescribing rate of rescue medication was reduced over the course of SCIT. Conclusion: These 'real‐life' data from a large retrospective analysis including 2927 children and adolescents with pollen‐ and/or mite‐induced allergic rhinoconjunctivitis with/or without allergic asthma indicate that AIT with depigmented polymerized extracts is well tolerated, and they are compatible with clinical response.